Visualizing opportunities: interview with Chris Harrison - Chris Harrison (Oz, 2010)
My formal training is as a computer scientist. I went to New York University, got my bachelors and masters degrees in computer science. So, I am sort of a traditional programmer on one end - and then, after working in the industry, I came back to work on my Ph.D. in a fairly new field called Human-Computer Interaction (HCI), which is often described as the intersection of computer science, design, and cognitive science or behavioral science.